2016
DOI: 10.1186/s12864-016-2505-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an extensive rainbow trout miRNA transcriptome by next generation sequencing

Abstract: BackgroundMicroRNAs (miRNAs) have emerged as important post-transcriptional regulators of gene expression in a wide variety of physiological processes. They can control both temporal and spatial gene expression and are believed to regulate 30 to 70 % of the genes. Data are however limited for fish species, with only 9 out of the 30,000 fish species present in miRBase. The aim of the current study was to discover and characterize rainbow trout (Oncorhynchus mykiss) miRNAs in a large number of tissues using next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 50 publications
7
54
0
Order By: Relevance
“…miR-133a) and one (miR-210) with unknown function. Based on our previously published miRNA repertoire (Juanchich et al, 2016), we confirmed miR-133a was expressed only in white muscle and showed that miR-210 had strong expression in white muscle. We also showed that miR-210 expression was upregulated during differentiation of satellite cells, suggesting that miR-210 was potentially involved in the differentiation of satellite cells.…”
supporting
confidence: 67%
See 3 more Smart Citations
“…miR-133a) and one (miR-210) with unknown function. Based on our previously published miRNA repertoire (Juanchich et al, 2016), we confirmed miR-133a was expressed only in white muscle and showed that miR-210 had strong expression in white muscle. We also showed that miR-210 expression was upregulated during differentiation of satellite cells, suggesting that miR-210 was potentially involved in the differentiation of satellite cells.…”
supporting
confidence: 67%
“…A 1 μg sample of total RNA was used for miRNA cDNA synthesis using a MystiCq MicroRNA cDNA RT kit (MIRRT, Sigma). For miRNA expression assays, forward primer sequences for miRNAs (miR-133a: TTGGTCCCCTTCAACCAGCTG; miR-210: AGCC-ACTGACTAACGTACATTG; miR-375: TTTGTTCGTTCGGC-TCGCGTTA) were taken directly from Juanchich et al (2016), and the universal reverse primer used for all miRNA expression analysis was provided with the MystiCq cDNA reverse transcription kit. For real-time RT-PCR assays of miRNA targets, a Step One Plus thermocycler (Applied Biosystems, Foster City, CA, USA) was used.…”
Section: Immunofluorescence Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 54 miRNAs (including mmu-miR-6352, hsa-miR-4785, hsa-miR-1305, and hsa-miR-5581) had never been reported as ovarian-predominant miRNAs in any vertebrate species. The expression of some miRNAs observed here in a tissue-dependent manner is consistent with previous results obtained in rainbow trout32. Similarly, it was recently demonstrated in humans that the majority of miRNAs was neither specific to single tissues nor housekeeping miRNAs.…”
Section: Discussionsupporting
confidence: 92%